3(w-7)-6=-3(-9w+7)-9w

Simple and best practice solution for 3(w-7)-6=-3(-9w+7)-9w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(w-7)-6=-3(-9w+7)-9w equation:


Simplifying
3(w + -7) + -6 = -3(-9w + 7) + -9w

Reorder the terms:
3(-7 + w) + -6 = -3(-9w + 7) + -9w
(-7 * 3 + w * 3) + -6 = -3(-9w + 7) + -9w
(-21 + 3w) + -6 = -3(-9w + 7) + -9w

Reorder the terms:
-21 + -6 + 3w = -3(-9w + 7) + -9w

Combine like terms: -21 + -6 = -27
-27 + 3w = -3(-9w + 7) + -9w

Reorder the terms:
-27 + 3w = -3(7 + -9w) + -9w
-27 + 3w = (7 * -3 + -9w * -3) + -9w
-27 + 3w = (-21 + 27w) + -9w

Combine like terms: 27w + -9w = 18w
-27 + 3w = -21 + 18w

Solving
-27 + 3w = -21 + 18w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-18w' to each side of the equation.
-27 + 3w + -18w = -21 + 18w + -18w

Combine like terms: 3w + -18w = -15w
-27 + -15w = -21 + 18w + -18w

Combine like terms: 18w + -18w = 0
-27 + -15w = -21 + 0
-27 + -15w = -21

Add '27' to each side of the equation.
-27 + 27 + -15w = -21 + 27

Combine like terms: -27 + 27 = 0
0 + -15w = -21 + 27
-15w = -21 + 27

Combine like terms: -21 + 27 = 6
-15w = 6

Divide each side by '-15'.
w = -0.4

Simplifying
w = -0.4

See similar equations:

| -21X-217=-12X-136 | | -12X-217=-12X-136 | | -11X-9=-7X-5 | | -19X-51=-12X-30 | | 8x-12=20x | | (2x+75)=(4x-25) | | 1+2(5x-3)=-2(6x-5)+4x | | (4x+18)=(7x-72) | | 4t^2-14t+35=0 | | -3X+7=-2X+4 | | 3/8*x=21/2 | | 4g+3=1g | | 3-2x=1000x | | 37w^2-312w-192924=0 | | (82.4-52)3/5=x | | -5X+13=-3X+7 | | (84.4-52)3/5=x | | z+72=8 | | 21X-39=13X-23 | | -11X-85=-6X-45 | | 6X-43=3X-22 | | 12X+134=6X+80 | | 3ln(x)+8=ln(3x)+12 | | 4psquared-12p+7=0 | | 45logx=3 | | 10X+36=6X+20 | | 34-9k=88 | | -5X-40=-3X-26 | | 2x^2-25x+80=0 | | -(3w+4)+5(w-2)-3(6w-8)=1 | | (x+35)=(3x+5) | | 10x^2+9x-117=0 |

Equations solver categories